(untitled) (Research, Society and Development, 2021)
PCC II are Psychosocial Care Centers with the objective of reinserting the subject in society, promoting autonomy and a comprehensive care for the subject. Thus, we observe that many users inserted in these services have Chronic Non-Communicable Diseases (NCDs), which are generally related to multiple causes and various risk factors that influence their daily lives, from an economic point of view, to their quality of life. individuals. The objectives of the present study are: to outline the profile of users assisted by the CAPS; to verify the prevalence of Chronic Non-Communicable Diseases with a focus on Systemic Arterial Hypertension (SAH) and Diabetes Mellitus (DM), in the presented sample; identify the risk factors present in the studied sample for the development of CNCDs. It is, therefore, a documentary, exploratory, descriptive and retrospective study with quantitative analysis. The collection took place retrospectively through the reception forms of a CAPS II unit, located in the city of Rio de Janeiro, from March to August 2020. The sample consisted of 81 users, of which only 29 had records about NCDs in their records, with a prevalence rate of 35.8%, the highest rate occurred in females, 40%. It concludes the need to streamline information about the clinical status of each user in order to provide comprehensive care, aimed at promoting health and continuity in the care of people with mental disorders.